Environmental, social, and governance scores and earnings management in telecommunication companies: An international perspective - Goksel Acar; Ali Coşkun (Financial Internet Quarterly, 2023)
This study investigates the relationship between environmental, social, and governance (ESG) scores and potential tendencies to manipulate the earnings of telecommunication companies. We assumed a negative relationship between ESG scores and earnings management since the companies with higher ESG are more responsible and expected to prevent manipulation. We used ESG scores from Refinitiv as sustainability measures and discretionary accruals as the indicator of earnings management. We constructed models assuming a bilateral relationship between ESG and earnings. The results reveal that companies with higher environmental scores have higher dispersion from normal accruals; this may result for two reasons in our anticipation: they may record more accruals depending on environmental regulations and may use environmental scores to make up their earnings. Social and governance scores have a negative impact on discretionary accruals, which are insignificant. Hence companies with higher social responsiveness and strong governance produce reliable financial information.
Keywords: F62; F63; G34; K32; L96; M41; 330; discretionary accruals; disclosures; earnings quality; ESG; telecommunication; sustainability